Congenital glaucoma - a severe form - Mariana Portela; Carmo Ferreira; Tiago Fernandes; Nicole Silva (Hygeia Press di Corridori Marinella, 2021)
Primary congenital glaucoma is a rare disease and results from malformations of the trabecular meshwork that determines the increase of intraocular pressure (IOP). It is characterized by a globe enlargement, corneal edema and opacification. It also is associated with rupture of Descemet's membrane with Haab's striae, thinning of the anterior sclera and iris atrophy, normally with IOP above 21 mmHg. We report a case of a full-term neonate girl in which a bilateral corneal opacity was observed. Ophthalmologic examination revealed corneal edema, Haab's striae and IOP of 37.3 mmHg in the right eye and 40 mmHg in the left eye. To achieve control of IOP, she performed sequential interventions: bilateral trabeculotomy; trabeculectomy and iridectomy on the left eye; and finally bilateral drainage implant. In this patient, despite early diagnosis and multiple surgical interventions, the severe presentation and poor response to surgical treatment with maintenance of high IOP establishes an obscure prognosis. The child needs frequent follow-ups.